Screening for psychotherapy readiness with the University of Rhode Island Change Assessment Scale and the Readiness for Psychotherapy Index - Hovmand, Oliver Rumle; Reinholt, Nina; Christensen, Anne Bryde; Bach, Bo; Arnfred, Sidse Marie (Frontiers in Psychology, 2025)
BackgroundIt is important to assess patients’ level of readiness before starting a course of psychotherapy, but only a few validated instruments are currently available for that purpose.MethodsPatients waiting for psychotherapy were administered the Danish translations of the University of Rhode Island Change Assessment Scale (URICA) and the Readiness for Psychotherapy Index (RPI) prior to commencing psychotherapy. We conducted confirmatory factor analysis of the instruments’ previously suggested factor structure, as well as evaluating the instruments’ ability to identify early adherence to psychotherapy by receiver operating characteristic (ROC) curves and regression analysis.ResultsOne hundred and fifty-five patients with emotional, personality, and post-traumatic stress disorders were included. The instruments showed poor to average psychometric properties and poor predictive validity regarding early adherence to psychotherapy.DiscussionFindings indicated that the Danish URICA and RPI possess average psychometric properties and have limited validity for predicting early adherence to psychotherapy in psychiatric outpatients awaiting psychotherapy.